The national-level stakeholder network for nutrition in India: An overview of results from a participatory mapping exercise - Partnerships and Opportunities to Strengthen and Harmonize Actions for Nutrition in India (International Food Policy Research Institute, 2013)
A key priority for the inception phase of POSHAN was to understand the landscape of actors involved in influencing program and policy decisions for nutrition, the links among actors, and the level of support and influence. This was done through a participatory stakeholder network mapping exercise, using a method 2 called Net-Map